2019
DOI: 10.5056/jnm18028
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated With Irritable Bowel Syndrome Development in Chinese College Freshmen

Abstract: Background/AimsThe role of psychosocial factors on irritable bowel syndrome (IBS) in adolescents is incompletely understood. The aim of this study is to investigate the association between the psychosocial factors and the risk of developing IBS in college freshmen. MethodsA cross-sectional survey was conducted in a randomly selected freshmen population in Wuhan China (n = 2449). Questionnaire evaluated demographics and psychosocial risks. The population was divided into 3 groups: non-discomfort, chronic abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…The current results showed significant differences between depressive symptom occurrence in IBS-PCOS vs. non-IBS-PCOS women, similar to the findings of a meta-analysis by Zhang et al, who demonstrated a more frequent occurrence and greater severity of depressive symptoms in IBS patients compared to controls (17). This is also consistent with Jiang et al, who observed that participants with IBS experienced more severe depression than individuals with chronic abdominal discomfort only (13).…”
Section: Ibs Pcos and Qol And Depressive Symptomssupporting
confidence: 92%
“…The current results showed significant differences between depressive symptom occurrence in IBS-PCOS vs. non-IBS-PCOS women, similar to the findings of a meta-analysis by Zhang et al, who demonstrated a more frequent occurrence and greater severity of depressive symptoms in IBS patients compared to controls (17). This is also consistent with Jiang et al, who observed that participants with IBS experienced more severe depression than individuals with chronic abdominal discomfort only (13).…”
Section: Ibs Pcos and Qol And Depressive Symptomssupporting
confidence: 92%
“…In patients with major depressive or anxiety disorders, the severity of the gastrointestinal symptoms could be based on the psychological status and could result in incorrect illness behavior [ 10 ]. An experience of psychosocial trauma is known to affect physical and mental health, and a significant number of FGID patients report psychosocial trauma and abuse [ 11 ]. In a study of a local community, the symptoms of IBS were significantly correlated with sexual, emotional, or verbal abuse that occurred throughout the childhood and adolescence, and symptoms of FD and FH were also associated with such abuse [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…4) Jiang et al, Emotional Schemas Questionnaire (2019): It has 10 questions, with scores in the 6-point Likert scale. Jiang et al (2019) reported a Cronbach's alpha coefficient of 0.893, which confirms its reliability. 5) Behavioral Cognitive Intervention with sleep health education: The intervention is based on a treatment plan adapted from "Cognitive-Behavioral Therapy for Generalized Anxiety Disorder" written by Dugas & Robichaud (2007) which was performed in 12 sessions of 90 minutes.…”
Section: Methodsmentioning
confidence: 64%
“…Irritable Bowel Syndrome is one of the most common and complicated of functional gastrointestinal diseases (Wang, Duan & Duan, 2018). Research shows that irritable bowel syndrome, due to its chronic and debilitating nature, has severe effects on the quality of life and increased use of health care services in these patients (Jiang et al, 2019;Mujagic et al, 2017). Also, some studies, in addition to weakness in various aspects of quality of life in these patients, have reported problems in the quality of sleep in these patients (Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%